Efficacy of temporally intensified exposure for anxiety disorders: A multicenter randomized clinical trial. Issue 11 (22nd July 2021) - Pittig, Andre; Heinig, Ingmar; Goerigk, Stephan; Thiel, Freya; Hummel, Katrin; Scholl, Lucie; Deckert, Jürgen; Pauli, Paul; Domschke, Katharina; Lueken, Ulrike; Fydrich, Thomas; Fehm, Lydia; et al.
Abstract: Background: The need to optimize exposure treatments for anxiety disorders may be addressed by temporally intensified exposure sessions. Effects on symptom reduction and public health benefits should be examined across different anxiety disorders with comorbid conditions. Methods: This multicenter randomized controlled trial compared two variants of prediction error‐based exposure therapy ( PeEx ) in various anxiety disorders (both 12 sessions + 2 booster sessions, 100 min/session): temporally intensified exposure ( PeEx‐I ) with exposure sessions condensed to 2 weeks ( n  = 358) and standard nonintensified exposure ( PeEx‐S ) with weekly exposure sessions ( n  = 368). Primary outcomes were anxiety symptoms (pre, post, and 6‐months follow‐up). Secondary outcomes were global severity (across sessions), quality of life, disability days, and comorbid depression. Results: Both treatments resulted in substantial improvements at post (PeEx‐I: d within  = 1.50, PeEx‐S: d within  = 1.78) and follow‐up (PeEx‐I: d within  = 2.34; PeEx‐S: d within  = 2.03). Both groups showed formally equivalent symptom reduction at post and follow‐up. However, time until response during treatment was 32% shorter in PeEx‐I (median = 68 days) than PeEx‐S (108 days; TRPeEx‐I  = 0.68). Interestingly, drop‐out rates were lower during intensified exposure. PeEx‐I was also superior in reducing disability days and improving quality of life at follow‐up without increasing relapse. Conclusions: Both treatment variants focusing on the transdiagnostic exposure‐based violation of threat beliefs were effective in reducing symptom severity and disability in severe anxiety disorders. Temporally intensified exposure resulted in faster treatment response with substantial public health benefits and lower drop‐out during the exposure phase, without higher relapse. Clinicians can expect better or at least comparable outcomes when delivering exposure in a temporally intensified manner.